2011
DOI: 10.1002/pssa.201100045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen addition on the crystal shape of CVD boron doped diamond

Abstract: The development of diamond based devices for high power electronic applications requires the growth of thick heavily boron doped diamond. During the growth of CVD single crystals, the final form of the film depends on the different crystalline faces growth rate with respect to each others. Three parameters (α, β and γ) which correspond to the displacement speeds of the {111}, {110} and {113} faces, normalized to the {100} displacement speed can be used into a 3D crystal growth model in order to predict the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…As reported in the literature , the lateral faces of the disk tend to disappear during the overgrowth, for the benefit of the top (0 0 1) face that expands. However, this tendency seems to be different between the SMC and LMC samples.…”
Section: Resultssupporting
confidence: 54%
“…As reported in the literature , the lateral faces of the disk tend to disappear during the overgrowth, for the benefit of the top (0 0 1) face that expands. However, this tendency seems to be different between the SMC and LMC samples.…”
Section: Resultssupporting
confidence: 54%
“…They noted that, as the oxygen concentration increased to 0.25%, the growth rate decreased because defective sites were formed on graphitic carbon layers, which were potential nucleation sites. Issaoui et al12 have also reported that the addition of a small amount of oxygen (0.25%) with boron can drastically change the growth rates in the different crystallographic directions. They mentioned that it is possible to inhibit the {110} faces formation and obtain a larger top surface area.…”
Section: Resultsmentioning
confidence: 99%
“…A small amount of oxygen from the solution (boron oxide + methanol) can also contribute to the growth rate variation. Oxygen is known to lead to potential chemical reactions with species in the gas phase and to the consumption of some carbon and boron species in the plasma, which usually reduces the diamond growth rate 12. Das et al13 have studied the effect of oxygen on the growth of non‐doped diamond films.…”
Section: Resultsmentioning
confidence: 99%
“…A small amount of oxygen from the solution (B 2 O 3 + methanol) can also contribute to the growth rate variation since with increasing boron doping in the gas mixture, the oxygen also increases. Oxygen is known to lead to potential chemical reactions with species in the gas phase and to the consumption of some carbon and boron species in the plasma, which usually modified the diamond growth rate [9]. The presence of oxygen from the solution in the growth gas mixture could be activated the intermediate species containing oxygen, which enhanced the etch rate of the nondiamond carbon component by improving the quality of the deposited film.…”
Section: Resultsmentioning
confidence: 99%